Penerapan Model Pembelajaran Kooperatif Menggunakan Media Kartu Truth and Dare untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas X.2 SMA Negeri 2 Barru - Iffah Nurfiati; Muhammad Wijaya; Army Auliah (ChemEdu, 2022)
Classroom action research (CAR) is intend to determine how to applicate the steps Cooperative Learning Model Using Truth and Dare Card Media to Improve Activities and Student Results in Class X2 SMAN 2 Barru. The subject of this researchof X2 that consist of 11 male and 15 female. This study is conduct by two cycles. The research data shows the steps of Cooperative Learning Using Truth and Dare Card Media is applied to improve the student learning outcomes Class X2 SMAN 2 Barru, Kab. Barru namely: (1) the teacher enter the classroom, say regards and prepare students to learn by checking the attendance list, (2) teacher extend to student learning objectives and student should be write in note book respectively, and then teacher is check its note, (3) student is read a book with hydrocarbon materials during 15 minutes, (4) the teacher explains the subject material of hydrocarbon and give question and answer to the students for know preliminary understanding after reading the book, (5) the teacher divides the students into five groups in heterogeneous by gender, activity in the classroom, and the students' cognitive abilities. Each group consisted of 5 students with composition 2 male and 3 female, (6) the teacher gives time for each group to answer questions from Truth or Dare card media during 2 minutes. If so, the question can be answered by another group who is complete the discussion. Teacher give the opportunity for everyone to ask if there are not understood during the discussion, (7) each group should have a summary of the answers to all the questions and the results of the teacher's explanations, (8) teachers evaluate individual with a test at the end of the cycle, (9) the teacher gives recognition or awards to the best groups and also to individuals who is active in the class.